The verb in Turkish - Taylan, Eser Erguvanlı (J. Benjamins Pub. Co., 2001)
This volume brings together research done on the clause structure of Turkish. It contains chapters on the major facets of the verb, each of which presents research on a certain aspect of the clausal structure of Turkish.
Keywords: Turkish language -- Verb.; FOREIGN LANGUAGE STUDY -- Turkish & Turkic Languages.; Turkish language -- Verb; Syntax; Aspekt -- Linguistik; Modus; Wortart; Verb; Verbalphrase; Tempus; Turks.; Werkwoorden.; Türkisch.